Influence of Impurity Atoms of Gallium and Antimony on the Concentration of Optically Active Oxygen in the Silicon Lattice - B. O. Isakov; B. R. Rakhmonov; Sh. N. Subkhonberdiev (International Journal on Orange Technologies, 2022)
The effect of impurity atoms of gallium and antimony on the concentration of optically active oxygen in the silicon lattice is studied. It is shown that the oxygen concentration in silicon samples doped with gallium decreases by 87.2%, doped with antimony decreases by 99.2%, and in the case of doping with gallium and antimony decreases simultaneously only by 28.7%. These results can be explained by the chemical interaction of gallium and antimony atoms, which leads to the restoration of the oxygen concentration in optical active centers.